Handover Analysis Of 4G LTE (Long Term Evolution) At A Frequency Of 2400 Mhz: - Akhyar, Al Habib Maulana; Afrizal Yuhanef; Dikky Chandra; Yulindon (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
Information technology has now become a primary need for many individuals, facilitating access to various needs, including work, learning, and other activities. Mobile phones allow users to stay connected to the internet without interruption, even when traveling out of town, thanks to their ability to switch between cells or through a process known as handover. The focus of this article is on the impact of handover on 4G LTE networks. The data collection approach in this research uses the drive test method by utilizing the tems pocket application to retrieve internet network data. The research results highlight the importance of understanding how handover can affect 4G LTE network performance. With the role of information technology increasingly dominating everyday life, a deep understanding of technical aspects such as handover has become essential to maintaining the quality and efficient availability of cellular communications services.